A multifunctional therapeutic approach to disease modification in multiple familial mouse models and a novel sporadic model of Alzheimer's disease. Issue 1 (December 2016) - Luo, Jia; Lee, Sue; VandeVrede, Lawren; Qin, Zhihui; Ben Aissa, Manel; Larson, John; Teich, Andrew; Arancio, Ottavio; D'Souza, Yohan; Elharram, Ahmed; Koster, Kevin; Tai, Leon; et al.
Abstract Background Clinical failures singularly targeting amyloid-β pathology indicate a critical need for alternative Alzheimer's disease (AD) therapeutic strategies. The mixed pathology reported in a large population of AD patients demands a multifunctional drug approach. Since activation of cAMP response element binding protein (CREB) plays a crucial role in synaptic strengthening and memory formation, we retooled a clinical drug with known neuroprotective and anti-inflammatory activity to activate CREB, and validated this novel multifunctional drug, NMZ, in 4 different mouse models of AD. Results NMZ was tested in three mouse models of familial AD and one model of sporadic AD. In 3 × Tg hippocampal slices, NMZ restored LTP. In vivo, memory was improved with NMZ in all animal models with robust cognitive deficits. NMZ treatment lowered neurotoxic forms of Aβ in both APP/PS1 and 3 × Tg transgenic mice while also restoring neuronal plasticity biomarkers in the 3 × Tg mice. In EFAD mice, incorporation of the major genetic AD risk factor, hAPOE4, did not mute the beneficial drug effects. In a novel sporadic mouse model that manifests AD-like pathology caused by accelerated oxidative stress in the absence of any familial AD mutation, oral administration of NMZ attenuated hallmark AD pathology and restored biomarkers of synaptic and neuronal function. Conclusions The multifunctional approach, embodied by NMZ, was successful in mouse models of AD incorporating Aβ pathology (APP/PS1), tau pathology (3xTg), andAPOE4, the major human genetic risk factor for AD (EFAD). The efficacy observed in a novel model of sporadic AD (Aldh2 −/− ) demonstrates that the therapeutic approach is not limited to rare, familial AD genetic mutations. The multifunctional drug, NMZ, was not designed directly to target Aβ and tau pathology; however, the attenuation of this hallmark pathology suggests the approach to be a highly promising, disease-modifying strategy for AD and mixed pathology dementia.